APPLICABILITY OF ASSISTED REPRODUCTION TECHNIQUES IN CONTEMPORARY SMALL RUMINANT FARMING - Dovenski T. , Petkov V. , Popovska-Percinic F., Atanasov B. , Ilievska K., Nikolovski M. , Dovenska M. , Trojacanec P. , Vince S. , GrizeljJ. (Faculty of Veterinary Medicine, University of Forestry, Bulgaria, 2017)
Sheep and goat breeding has long tradition in the Balkan countries, making it leading trade in animal husbandry. Dynamic changes in global agriculture production from traditional to industrial livestock technologies, has also impacted the small ruminant farming systems. The reproduction management is considered to be a crucial point for good farming practice among other animal husbandry factors (housing, nutrition, selection, healthcare, etc.). In the last few decades, our sheep and goat farming systems have introduced various assisted reproduction techniques, such as estrous and ovulation synchronization, laparoscopic intrauterine insemination, embryo production (MOET and IVF), semen cryoconservation, photoperiod manipulation etc. This article reviews the current novelties in this field, presenting worldwide scientific reports and our personal experiences in research and translation to everyday farm practice. Ovine and caprine species have been considered as typical seasonal breeders, becoming sexually active as result of pineal gland and day-length alterations in late summer/early autumn. Lambing/kidding and milk production follow established seasonal patterns. In order for farmers to yield these productive traits in various seasons of the year, they are able to use different hormonal combination of progestagens, prostaglandins, exogenous gonadotropins (eCG) or “natural” methods: light control or exposure to a male after period of isolation (“ram/buck effect”). The hormonal treatment by vaginal sponges is applicable throughout the year, resulting in pregnancy and higher lambing rates compared to seasonal breeding (see review Dovenski and Gvozdic 2012). The implementation of most recent Artificial Insemination techniques in small ruminants, suggests that the transcervical insemination success rates could be improved by intracornual deposition of semen (laparoscopy), bypassing the “cervical barrier”. Our results indicate high pregnancy rates could be obtained by Intrauterine Laparascopic Insemination in sheep (45% out of season, 60% during the breeding season) and even higher in goats 70-80% (Dovenski at al. 2012). Some attempts for pharmacological relaxation of uterine cervix in sheep with unsatisfactory success have been also reported by Candappa et al (2009). Survival rate of buck’s spermatozoa has been dramatically improved by using the “egg-yolk free” extenders, based of soya lecithin as cryoprotectant. Conversely, ram semen cryopreservation did not make substantial progress in past decades, despite the great research work in testing of novel media supplemented by various antioxidants (oxidized glutathione, reduced glutathione, cysteine), and the peculiar in-vivo trials which has shown optimistic results.
Keywords: assisted reproduction, sheep, goats, artificial insemination, estrous synchronization